Refugial persistence and postglacial recolonization of North America by the cold‐tolerant herbaceous plant Orthilia secunda - GEMMA E. BEATTY; JIM PROVAN (Molecular Ecology, 2010)
Previous phylogeographical and palaeontological studies on the biota of northern North America have revealed a complex scenario of glacial survival in multiple refugia and differing patterns of postglacial recolonization. Many putative refugial regions have been proposed both north and south of the ice sheets for species during the Last Glacial Maximum, but the locations of many of these refugia remain a topic of great debate. In this study, we used a phylogeographical approach to elucidate the refugial and recolonization history of the herbaceous plant species Orthilia secunda in North America, which is found in disjunct areas in the west and east of the continent, most of which were either glaciated or lay close to the limits of the ice sheets. Analysis of 596 bp of the chloroplast trn S‐ trn G intergenic spacer and five microsatellite loci in 84 populations spanning the species’ range in North America suggests that O. secunda persisted through the Last Glacial Maximum (LGM) in western refugia, even though palaeodistribution modelling indicated a suitable climate envelope across the entire south of the continent. The present distribution of the species has resulted from recolonization from refugia north and south of the ice sheets, most likely in Beringia or coastal regions of Alaska and British Columbia, the Washington/Oregon region in the northwest USA, and possibly from the region associated with the putative ‘ice‐free corridor’ between the Laurentide and Cordilleran ice sheets. Our findings also highlight the importance of the Pacific Northwest as an important centre of intraspecific genetic diversity, owing to a combination of refugial persistence in the area and recolonization from other refugia.